An Evaluation of the Use of People Analytics and Talent Management in Improving Human Resource Quality and Productivity in Manufacturing Companies in West Java - Nanda Hidayati; Ilham Akbar Bunyamin; Paramita Andiani (West Science Interdisciplinary Studies, 2026)
This study aims to evaluate the use of people analytics and talent management in improving the quality and productivity of human resources in manufacturing companies in West Java. The rapid development of digital transformation and Industry 4.0 has encouraged manufacturing organizations to adopt data-driven human resource management practices to enhance operational efficiency and workforce competitiveness. This study uses a quantitative research approach involving 150 respondents from manufacturing companies in West Java. Data were collected through questionnaires using a Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3 software. The variables examined include people analytics, talent management, human resource quality, and human resource productivity. The results indicate that people analytics has a positive and significant effect on human resource quality with a path coefficient of 0.381 and a T-statistic of 5.842. Talent management also positively affects human resource quality with a path coefficient of 0.472 and a T-statistic of 7.116. Furthermore, human resource quality significantly influences human resource productivity with a path coefficient of 0.844 and a T-statistic of 18.527. The findings demonstrate that the integration of people analytics and talent management contributes significantly to improving workforce competency, professionalism, and productivity in manufacturing organizations. This study provides theoretical contributions to human resource management literature and practical implications for manufacturing companies in developing data-driven HR strategies and sustainable talent development systems to improve organizational competitiveness.